Anti-Hyperglycemic and Anticholinergic Effects of Natural Antioxidant Contents in Edible Flowers - Paulina Nowicka; Aneta Wojdyło (MDPI AG, 2019)
In this study, 16 selected edible flowers were evaluated for their content of bioactive compounds (polyphenols, carotenoids, triterpenoids) and for their anti-diabetic (ability to inhibit α-amylase and α-glucosidases) and anti-aging (ability to inhibit acetylcholinesterase and butyrylcholinesterase) activities. Most of the flowers analyzed in this study have not been examined in this respect until now. Contents of the analyzed bioactive compounds differed significantly among the flowers. In particular, the highest contents of carotenoids and triterpenoids were determined in marigold, arnica, lavender, and daisy; in turn, the highest contents of phenolic acids, procyanidin polymers, and total polyphenols were assayed in hawthorn, primrose, and linden blossom. There was a positive correlation between the content of isoprenoids in edible flowers and their anti-aging activity, and between the content of polymeric procyanidins and flowers’ ability to inhibit α-glucosidase. In conclusion, edible flowers may be used to produce functional foods as well as for medical purposes.